Out of control : why disciplining your child doesn't work--and what will - Tsabary, Shefali, 1972- (Namaste Publishing, 2013)
Tsabary reveals how the very discipline we impose to control behavior is in reality a major cause of bad behavior, disrespect for adults, and dysfunction such as bullying, drugs, and teen suicide. She advocates for a high level of parental resolve that helps a child develop a sense of personal responsibility.